Study on the slurry ability and combustion behaviour of coal‐bioferment residue of drugs‐slurry. (26th September 2017) - Wang, Jinqian; Liu, Jianzhong; Jin, Yuqi; Li, Dedi; Cen, Kefa
Abstract: Bioferment residue of drugs (BRD) is one kind of harmful and hazardous substance which has complex compositions. Thus, proper treatment of these residues has become an important concern. BRD can be utilized harmlessly and economically by mixing it with coal powder, water, and dispersant to prepare slurry fuel, named as coal‐BRD‐slurry (CBRDS). In this study, the influence of BRD on the slurry ability and combustion behaviour of CBRDS was investigated with coal water slurry (CWS) as reference. Results showed that the dispersant can reduce the slurry viscosity of CBRDS and CWS, and its optimum dosage was 0.6 wt% on the dried coal basis. The fixed‐viscosity concentration of CBRDS decreased with increasing BRD dosage. CBRDS and CWS exhibited shear‐thinning behaviour. The rheological behaviour was fitted by the power law. CBRDS exhibited higher apparent viscosity and stronger shear‐thinning behaviour because of the flocculent structure and well‐developed pores of the BRD. BRD can improve the stability of CWS by decreasing solid‐liquid separation of the slurry. Addition of BRD decreased the ignition temperature and increased the ash residues, suggesting a synergistic effect of CWS and BRD occurred during the combustion of CBRDS.